2003
DOI: 10.1017/s0952523803203102
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of shape representation in macaque visual area V2

Abstract: Contours and surface textures provide powerful cues used in image segmentation and the analysis of object shape.To learn more about how the visual system extracts and represents these visual cues, we studied the responses of V2 neurons in awake, fixating monkeys to complex contour stimuli (angles, intersections, arcs, and circles) and texture patterns such as non-Cartesian gratings, along with conventional bars and sinusoidal gratings. Substantial proportions of V2 cells conveyed information about many contour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 57 publications
(54 reference statements)
3
37
0
Order By: Relevance
“…The current line of thought is that shape preferences and tolerance to object transformations build up gradually as we ascend the visual hierarchy (24,85,107,108). Consistent with this notion, neurons in areas V2 and V4 typically show larger receptive fields and responses to more complex shapes than do neurons in V1 but smaller receptive fields and less complexity and tolerance to object transformations than neurons in the ITC (109)(110)(111)(112). Much more work is needed to elucidate the computations that lead to shape recognition along the ventral visual pathway.…”
Section: Figuresupporting
confidence: 55%
“…The current line of thought is that shape preferences and tolerance to object transformations build up gradually as we ascend the visual hierarchy (24,85,107,108). Consistent with this notion, neurons in areas V2 and V4 typically show larger receptive fields and responses to more complex shapes than do neurons in V1 but smaller receptive fields and less complexity and tolerance to object transformations than neurons in the ITC (109)(110)(111)(112). Much more work is needed to elucidate the computations that lead to shape recognition along the ventral visual pathway.…”
Section: Figuresupporting
confidence: 55%
“…Primate neurophysiology indicates that there are populations of V2 neurons selectively sensitive to angles (Anzai, Peng, & VanEssen, 2007;Hegdé & Van Essen, 2003). In addition, recent fMRI evidence has shown that the human parahippocampal place area (PPA) responds strongly to triangles, squares, and hexagons, but not to circles or dodecagons (Nasr, Echavarria, & Tootell, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that a more complete representation of object shapes must include contours incorporating sharp angles. In support of this, macaque V2 has also been reported to contain groups of neurons most sensitive to a range of angles (Anzai, Peng, & VanEssen, 2007;Hegdé & Van Essen, 2003). Therefore, the goal of this paper is to introduce a novel class of visual shapes that are formally analogous to RF patterns, but differ in being defined by sharp angles indicative of polygons.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, an indirect approximative test of the selectivity can be performed by considering the responses of measured and simulated nonlinear neurons to large test set of stimuli, and compare these to the responses of linear neurons. Extended test sets like the one used in Figure 16 have been employed for the analysis of V2 and V4 neurons (Gallant et al 1993;Hegde & van Essen 2003). We have used simulated nonlinear neurons that have been learned in the two-stage scheme shown in Figure 3 and described in Zetzsche & Röhrbein (2001) in a version with two resolution layers, four orientations, and even-and odd-symmetric filters, and applied these nonlinear neurons to the stimulus test set.…”
Section: Higher-order Representations In V2 and V4 And Nonlinear Invamentioning
confidence: 99%